Kirkpatrick’s Approach to Build Faculty Development Programs in Medical Education - Sundas Ahmad, Mavra Imtiaz, Rao Salman Aziz, Nusrat Manzoor, Shoaib Ahmed, Bilal Habib (Pakistan Journal of Medical & Health Sciences, 2023)
This article demonstrates how to create, manage, and administer a comprehensive faculty development programme utilising the Kirkpatrick model. The academic literature lacks discussion and analysis of how faculty development might improve healthcare faculty in all academic domains. This study shows that the Kirkpatrick model may be used to create and manage institutional faculty development programmes, filling a gap in the academic literature. If medical schools priorities staff development in line with their mission, they can become more competitive and serve their students better. Healthcare students will benefit from this. Place of Study: Rai Medical College Sargodha Study Duration: June 2021 to February 2022 Study Design: Empirical research Conclusion: This article suggests that faculty development should be done methodically and to fit the needs of various faculty groups. It also suggests that the educators’ ultimate purpose is to train medical business executives who can handle the challenges of modern medicine on their own. Medical education programmes must adapt to changing stakeholder needs, focusing on outcomes rather than instruction. Keywords: Faculty Development Program, Medical Education, Kirkpatrick’s Model, Teaching Performance, Effectiveness